A Analysis of Geographic Information Design for Hotel Locations in Lau Gumba Village Based on Android: Analysis of Geographic Information Design for Hotel Locations in Lau Gumba Village Based on Android - Muhammad Amin; Chairul Rizal; Adityia Rama Sanjaya (Sean Institute, 2022)
Lau Gumba Village is a village located in Brastagi District, Karo Regency, North Sumatra Province which is quite well known because it has quite interesting tourist objects to visit. The information system that presents information on tourist attractions in the village only displays pictures and names which are presented in the form of maps, newspaper and web advertising media that do not provide direct instructions to the destination tourist location. The problem obtained from the media information for tourists is that they do not get direct instructions on the location of the tourist attraction geographical position. This requires technology that can present tourist attraction information, namely Geographic Information Systems (GIS). So that tourists who want to travel to Lau Gumba Village but still don't know the location or place of an interesting tourist attraction to visit can be known by tourists who will visit. To overcome this problem the author uses an approach to a digital mapping model in the form of a GIS (Geographical Information System) based on an Android mobile using Google Maps as a digital map. The method used in this research is using UML (Unifed Modeling Language), PHP program, java and MySQL database as data storage. The Geographic Information System (GIS) for natural tourism objects has two programs, namely an admin program to manage web-based tourism data and a user program to display android-based tourist objects. This geographic information system aims to provide convenience and speed to the public in obtaining information about Natural Tourism Objects in Lau Gumba Village.